Bibliometric Analysis of Islamic Banking Literature Published in Times of Covid-19 Pandemic - Muhammad Raihan Gunawan; Aam Slamet Rusydiana (Al Tijarah, 2022)
This study aims to analyze articles with the subject matter of Islamic Banking published during the 2020-2021 period in times of the Covid-19 Pandemic and indexed by Scopus (https://scopus.com) on an analysis of articles, authors, journals, and keywords. The papers analyzed were as many as 681 documents using bibliometric analysis with the help of R Biblioshiny software. The numbers showed the researcher's high desire to research with the theme of Islamic Banking during the pandemic. The author who often studies this theme is Hassan MK. Most journals published on Islamic Banking during covid-19 are "Journal of Islamic Marketing" and "Journal of Islamic Accounting and Business Research." Several themes related to Islamic Banking research, namely corporate social responsibility, profitability, efficiency, financial crisis, and Islamic finance. However, the trend analysis shows that few researchers have linked Islamic Banking research to these themes. Therefore, a study with these themes needs development considering the limited research that extensively addresses the Islamic Banking theme in Islamic economics and finance research.